A randomized controlled trial assessing behavioral, cognitive, emotional and physiological changes resulting from a communication skills training in physicians caring for cancer patients. Issue 9 (September 2022) - Libert, Yves; Peternelj, Livia; Bragard, Isabelle; Marchal, Serge; Reynaert, Christine; Slachmuylder, Jean-Louis; Razavi, Darius
Abstract: Objective: This randomized study assesses behavioral, cognitive, emotional and physiological changes resulting from a communication skills training (CST) for physicians caring for cancer patients. Methods: Medical specialists (N = 90) were randomly assigned in groups to complete a manualized 30-h CST or to a waiting list. Assessments included behavioral (communication skills), cognitive (self-efficacy, sense of mastery), emotional (perceived stress) and physiological (heart rate) measures. Assessments were made at baseline (both groups), after CST program (training group), and four months after (waiting list group). All assessments were conducted before, during, and after a complex communication task with an advanced-stage cancer simulated patient (SP). Results: Trained physicians had higher levels of communication skills (from RR=1.32; p  = .003 to RR=41.33; p  < .001), self-efficacy (F=9.3; p  = .003), sense of mastery (F=167.9; p  < .001) and heart rate during the SP encounter (from F=7.4; p  = .008 to F=4; p  = .050) and same levels of perceived stress (F=3.1; p  = .080). Conclusion: A learner-centered, skills-focused and practice-oriented manualized 30-h CST induced multilevel changes indicating physician engagement in a learning process. Practice implications: Trainers should consider the CST multilevel benefits (behavioral, cognitive, emotional and physiological) before, during and after a complex communication simulated task as an innovative way to assess the efficacy of a communication skills learning process. Highlights: Behavioral, cognitive, emotional, physiological changes resulted from a CST. The efficacy of CST has been showed on multilevel changes. CST changes indicating physician engagement in a learning process. CST changes indicating physician acquisition of mastered communication skills.